Supporting landscape-scale planning with decision support toolkits - Crist, Patrick, speaker; Anderson, David, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Conservation decisions often come down to actions by individual private landowners, whether it be acquisition of easements, land or development rights; outreach and education, assistance with restoration, etc. To target the locations that will offer the most conservation benefit, it is useful to put decisions into a larger landscape context. A broader context can help identify areas that can conserve the most valuable areas with least conflicts and perhaps lower cost; in other words, a larger context provides more options. However, there is often a disconnect between conservation plans developed at broad scales of landscapes or ecoregions and implementation that must happen at the site scale. This disconnect can happen for many reasons, one being that broad-scale plans are often developed using coarser data or planning units that may not be informative to site-level decision making. This presentation will illustrate with real-world examples the application of decision support toolkits that are able to support both landscape-scale assessment and prioritization, and site-level decision making. This is accomplished through the use of a framework planning tool, NatureServe Vista that, unlike many conservation tools, retains data in its source resolution. Vista can facilitate cumulative effects assessment and landscape prioritization; then be used to explore, assess, and plan actions for individual sites. In this presentation we will illustrate the multi-scale application for both coastal and inland areas.
Moderator: David Anderson.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
September 11, 2014.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses